New Quality Productivity and Chinese Modernization: Analysis based on the Perspective of Scientific and Technological Innovation - Li, Lingui; Liu, Li (International Journal of Social Sciences and Public Administration, 2024)
New quality productivity is an advanced productivity quality that conforms to the new development concept and has the characteristics of high technology, high efficiency, and high quality. On the new journey of promoting high-quality development of Chinese modernization, we must accelerate the release of innovation momentum, insist on leading development with scientific and technological innovation, and promote the construction of a strong country and national rejuvenation with the development of the aerospace industry. New productivity has important contemporary value and practical significance for empowering commercial aerospace and low-altitude economy, vigorously promoting the spirit of aeronautical patriotism and the spirit of the manned space program, and promoting the high-quality development of Chinese modernization through self-reliance and self-reliance in high-level aerospace science and technology. Under the background of increasingly fierce global scientific and technological competition, China needs to follow the law of the formation and development of productive forces, explore the development path of new quality productive forces, and strengthen the innovative quality of Chinese modernization.